'I felt paralysed to ask for help for myself': domestic abuse experienced by healthcare professionals. Issue 4 (April 2023) - Gregory, Alison; Howell, Annie; Johnson, Medina; Potter, Lucy C; Dheensa, Sandi
Domestic abuse is widespread and disproportionately affects women. However, it can affect anybody, regardless of gender, sexuality and socioeconomic status. This includes healthcare professionals, who are often tasked with the responsibility to identify and respond to domestic abuse among their patients. Recent research suggests that healthcare professionals may be more likely to experience domestic abuse than people in the general population: this research also indicates that healthcare staff members are less able to seek support.